Evaluation of the Radiochemical Purity of Technetium-99m Radiopharmaceuticals: A Decade of Experience in an Accredited Laboratory - A. O. Malysheva; E. A. Lyamtseva; A. A. Larenkov (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION. The most important quality indicators of a radiopharmaceutical (RPh) are its radiochemical purity (RCP) or radiochemical impurity content (RCI), the values of which are standardized. Mandatory control testing of lyophilisates to assess composition, authenticity, apyrogenicity, and sterility is guaranteed by the manufacturer. Evaluation of the technetium-99m labeling process for lyophilisates, which can be influenced by numerous factors, is usually the responsibility of the end user. The methods presented in quality regulatory documents were developed in the 1970s and 1980s, and some of them require adjustment due to the upgrading of measurement instrumentation and the emergence of new materials. AIM. To summarize the 10-year experience (2015–2025) of an accredited testing laboratory by analyzing the quality control results of 99m Tc-RPhs routinely used in clinical practice, to adjust existing analytical methods specified in manufacturers’ quality documents, and to develop new ones. MATERIALS AND METHODS. Quality control of technetium-99m radiopharmaceuticals was performed using the most significant parameters, RCP/RCI, following the methods presented in the approved quality documents of the manufacturers. The radiopharmaceuticals were prepared from lyophilisates and eluate (Na 99m TcO 4 solution) from 99 Mo/ 99m Tc generators of the GT-2M, GT-4K, and GT-5K types. RESULTS. During the 10 years of operation, the accredited laboratory tested 1106 radiopharmaceuticals. Analytical methods for determining RCP/RCI based on thinlayer chromatography (TLC) were identified and tested for the radiopharmaceuticals “Macrotech, 99m Tc,” “Bromezida, 99m Tc,” and “Pentatech, 99m Tc,” replacing the previously used filtration and high-voltage agarose gel electrophoresis methods. For the radiopharmaceutical “Technemek, 99m Tc,” a chromatographic method was tested instead of determining the radiochemical composition indicator. This method allows simultaneous determination of the technetium-99m complex with dimercaptosuccinic acid (retardation factor, R f 0.45–0.70), free Na 99m TcO 4 (R f 0.9–1.0) and hydrolyzed reduced technetium-99m (R f 0–0.15). CONCLUSIONS. Of the total number of radiopharmaceuticals tested over the 10-year period, only a limited number of radiopharmaceuticals (3.2%) had an RCP below the acceptable level. The advantages of the proposed methods lie in the simplification of the analytical procedures, which will allow their use in a medical facility immediately before administration of the radiopharmaceutical to the patient, as well as reliable determination of the most important quality indicator of the radiopharmaceutical (RCP), which is responsible for accumulation in the target organ. The developed methods can be proposed for inclusion in draft pharmacopeial monographs and to the manufacturers of lyophilisates for their incorporation into quality regulatory documents.